Rehabilitation Using Kinect and an Outlook on Its Educational Applications: A Review of the State of the Art - Reis, Helena M.; Wiechmann, Lucas; Borges, Simone S.; Gasparini, Isabela; Tsutsumi, Monike; Brandão, Alexandre F.; Vasilceac, Fernando A.; Gonçalves, Adriana Garcia; R. Filho, Ramílio R.; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2015: Anais do XXVI Simpósio Brasileiro de Informática na Educação, 2015)
Rehabilitation using the Kinect technology and systems for educational purposes can influence patient's motivation. However, approaches that use these two aspects together are poorly investigated. To provide an overview and understanding of the results already obtained in this area, a systematic mapping study was conducted in order to analyze how the rehabilitation using Kinect technology has been investigated. In total, 156 studies were analyzed corresponding to 4 years of research in the area of rehabilitation using Kinect. Among these, 51 studies were related to the development of interfaces and only 50 of them satisfied the inclusion and exclusion criteria defined in this work. As a result, we verified that most of the studies have investigated physical rehabilitation of upper body part. Moreover, the most investigated system type was serious game. We also identified that there are opportunities to research for rehabilitation in educational field.